Fundamental aspects of leverage, profitability and financial distress as mediating variables that influence firm value - Sri Hermuningsih; Teguh Erawati; Anisya Dewi Rahmawati; Hadri Kusuma (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
This research aims to examine how leverage and equity affect firm value and financial distress as mediating factor in listed manufacturing firms on the Indonesia Stock Exchange. Such manufacturing businesses are the research's population. The manufacturing industry is the research sample from 2011 to 2021 periods. Purposive sampling was utilized in the sampling approach, resulting in data availability from 53 firms and 583 financial statement data—a structural equation model with structural equations for hypothesis testing. The test results demonstrate that leverage affects financial distress. Financial distress is negatively impacted by profitability. Leverage and financial distress negatively affect both firm value and financial distress, acting as a mediating factor. Conversely, profitability positively affects both firm value and financial distress, functioning as a mediating factor.